Testing Regulatory Regimes for Power Transmission Expansion with Fluctuating Demand and Wind Generation - Wolf-Peter Schill; Jonas Egerer; Juan Rosellón (Journal of Regulatory Economics, 2015)
Adequate extension of electricity transmission networks is required for integrating fluctuating renewable energy sources, such as wind power, into electricity systems. We study the performance of different regulatory approaches for network expansion in the context of realistic demand patterns and fluctuating wind power. In particular, we are interested in the relative performance of a combined merchant-regulatory price-cap mechanism compared to a cost-based and a non-regulated approach. We include both an hourly time resolution and fluctuating wind power. This substantially increases the real-world applicability of results compared to previous analyses. We show that a combined merchant-regulatory regulation, which draws upon a cap over the two-part tariff of the transmission company, leads to welfare outcomes superior to the other modeled alternatives. This result proves to be robust over a range of different cases, including such with large amounts of fluctuating wind power. We also evaluate the outcomes of our detailed model using the extension plans resulting from a simplified model based on average levels of load and wind power. We show that this distorts the relative performance of the different regulatory approaches.
Additional information: The final publication is available at Springer via http://dx.doi.org/10.1007/s11149-014-9260-0
Keywords: L50; L94; Q40; 330; Electricity transmission; Incentive regulation; Renewable integration; Europe; Windenergie; Elektrizität; Regulierung